Errors in the Formation of Präteritum for Regular and Irregular Verbs in Student's Essays in Aufsatz II Course State University of Malang - Jeni Sintia Hunga Meha; Rosyidah Rosyidah (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2022)
This study aims to describe the errors in the formation of Präteritum for regular and irregular verbs in student essays in Aufsatz II course and the factors that cause them. The data were collected using documentation and questionnaire techniques, then the data were analyzed using a qualitative descriptive approach. Based on the results of the study, it was concluded that there were still many Offering A students class 2017 who had difficulties and made mistakes in forming Präteritum for regular verbs (regelmäβiges Verb) and irregular verbs (unregelmäβiges Verb) when writing essays. Factors causing students to make errors in the formation of Präteritum in essays in the Aufsatz II course include: (1) lack of understanding of the use of Präteritum for regular and irregular verbs, (2) lack of understanding of the formation of Präteritum for regular and irregular verbs, and (3 ) forgot the rules for forming Präteritum, especially for irregular verbs.